Comparison of the Effects of Hydration with Water or Isotonic Solution on the Recovery of Cardiac Autonomic Modulation - Vanderlei, Franciele Marques; Moreno, Isadora Lessa; Marques Vanderlei, Luiz Carlos [UNESP]; Pastre, Carlos Marcelo [UNESP]; Abreu, Luiz Carlos de; Ferreira, Celso (Human Kinetics Publ Inc, 2015)
Despite the importance of hydration during exercise, the impact of ingesting water or isotonic solution during and after exercise on the regulation of autonomic modulation is unclear. The study aimed to compare the effect of ingesting water or isotonic solution (Gatorade (R), Brazil) on cardiac autonomic modulation in young people after submaximal aerobic exercise. Thirty-one young men were subjected to a protocol consisting of 4 steps: 1) incremental test, 2) control protocol without hydration, 3) protocol with ingestion of water, and 4) protocol with ingestion of isotonic solution. The protocol consisted of 10 min of rest, 90 min of treadmill exercise at 60% VO2peak, and 60 min of recovery at rest. In the hydration protocols, hydration occurred during and after exercise, every 15 min beginning after the 15th minute of exercise, with the amount ingested proportional to body mass lost in the control protocol. Autonomic modulation was evaluated by heart rate variability. The hydration protocols promoted a more efficient recovery of autonomic modulation, and for the exercise performed, regardless of the hydration administered, the effect on autonomic modulation was similar.
Keywords: aerobic exercise; rehydration solutions; autonomic nervous system; recovery of physiological function; heart rate variability